IRI-2001 MODELİ İLE ELDE EDİLEN F2-BÖLGESİNİN MAKSİMUM ELEKTRON YOĞUNLUĞUNUN İNCELENMESİ - SAĞIR, SELÇUK (Fırat Üniveristesi, 2008)
İyonküre plazmasının en önemli parametresi F2 Bölgesinin maksimum elektron yoğunluğu (NmF2) dir. Maksimum elektron yoğunluğu iyonkürenin kendi iç dinamikleri ve dış etkenlere bağlıdır. Bu parametrelere bağlı olarak elektron yoğunluğu yüksekliğe, enleme, mevsime ve yerel zamana bağlı olarak değişir. İyonkürenin maksimum elektron yoğunluğu deneysel olarak ölçüldüğü gibi teorik olarakda elde edildiği modeller vardır.Bu çalışmada, (51,70 °K; 2, 33 °B) coğrafik koordinatında (Chilton istasyonunda) ölçülen NmF2 değerleri ile aynı coğrafik koordinatlarda IRI-2001 (International Reference Inosphere) modeli kullanılarak hesaplanan NmF2 değerleri mevsimsel ve yıllık olarak incelenmiştir.Ölçülen ve hesaplanan maksimum elektron yoğunlukları farklı yıl, mevsim ve günler için karşılaştırılmıştır. IRI-2001 programı ile hesaplanan F2 Bölgesi maksimum elektron yoğunluğu ile ölçüm sonuçları arasında genel olarak bir uyumun olduğu görülmüştür. Bu durum korelasyon katsayısı ile verilmiştir.Anahtar kelimeler: Elektron yoğunluğu, Kritik frekans, İyonküre

The most important parameter at F2-region of ionosphere is the maximum electron density (NmF2). The maximum electron density depends on both the internal dynamics of ionosphere and external factors in the ionospheric plasma. The maximum electron density as depending on these parameters varies with respect to altitude, latitude, seasonal and local time in ionospheric plasma. As the maximum electron density measures as experimental, there are various models to calculate the maximum electron density.In this study, the measured and calculated of the NmF2 values using IRI-2001 model at geographic coordinates (51,70 °K; 2, 33 °B) over Chilton Station have been investigated as seasonal and annual. The NmF2 values were calculated by using IRI-2001 model for same coordinates. The values of measured and calculated were compared for different years and seasonal.The changes of measured and calculated maximum electron density have also been investigated as seasonal and annual. There is an exact harmony between the results of calculated maximum electron density with IRI-2001 model and measured at F2-region in ionospheric plasma. The harmony has been given by correlation coefficients.Keywords: Electron density, Critical frequency, Ionosphere
The investigation of maximum elektron density of the F2 region obtained with IRI-2001 model
Keywords: Fizik ve Fizik Mühendisliği